Reproductivity and reising of Greater Rhea (Rhea americana) and Lesser Rhea (Pterocnemia pennata). A review - Navarro, Joaquin Luis (2002)
The Greater or Common Rhea (Rhea americana) and theLesser or Darwin’s Rhea (Pterocnemia pennata) are flight-less birds native from South America, that have conserva-tion and economic importance. Free-ranging populationsof these ratites have been detrimentally affected by humanactivities (BucherandNores, 1988;Carman, 1988;Martellaet al., 2000). On the other hand, during the1990s the farming of ratites, including rheas, experimenteda boom-and-bust process in USA, Canada and some Eur-opean countries (ChapmanandBass, 1994;Nara, 1994a;DeemingandAngel, 1996;Carbajoet al., 1997;Castel-lo ́, 1998a;Dey, 1998;GillespieandSchupp, 1998).